Convertire e disciplinare Chiesa romana e religiosità popolare in età moderna - Cattaneo, Massimo (Clio. Essays in History, Archaeology and Art History, 2022)
Converting and disciplining, these are the two key words of the book. Starting with the Lutheran Reformation, the Church of Rome realised the need both to defend itself against its enemies, old and new, external and internal, and to 'Christianise' its own faithful, to put in order the numerous contradictions that existed between doctrinal prescriptions and the concrete religious experience of the faithful. The instruments used were many, from confraternities to missionaries, inquisitors, the rediscovery of the first martyrs and the catacombs. What emerges, from the many sources used in the text, is an unruly Christianity, often unaware even of basic dogmas. Through various case studies, the reader is presented with a religious history of the modern age, and in particular of the 18th century, used as a passepartout to understand the changes in popular mentality at a time when the Church was gradually forced to redesign its role in society.